Epileptiform EEG discharges during sevoflurane anesthesia in children: A meta-analysis. (November 2022) - Miao, Mengrong; Han, Yaqian; Zhang, Ying; Xu, Yuehua; Zhang, Liyuan; Yang, Yitian; Sun, Mingyang; Zhang, Jiaqiang
Highlights: Sevoflurane is widely used in general anesthesia, but presents epileptiform EEG discharges during anesthesia in children. This meta-analysis presents the incidence and factors associated with epileptiform EEG discharges during sevoflurane anesthesia in children. The current evidence indicates that epileptiform EEG events are common in children during sevoflurane anesthesia and should catch the clinicians' attention. Abstract: Objective: To investigate the overall incidence and associated factors of epileptiform discharges in children during sevoflurane anesthesia. Methods: Our group systematically searched the PubMed, Cochrane library (Central) and EMBASE for the relevant trials from their inception until September 2020. The primary endpoint was the incidence of epileptiform discharges during sevoflurane induction. The secondary endpoints were the incidence of different types of epileptiform discharges, factors associated with these epileptiform events, and other adverse events such as seizure-like movements. Results: After screening of 713 records, eleven studies involving 448 participants were included into the final analysis. Meta-analysis indicated that the overall incidence of Epileptiform EEG discharges was 38.1% (95%confidence interval [CI], 19.1%-59.2%) during sevoflurane anesthesia in children. Subgroup analysis showed that the incidence of these EEG patters was lower when participants were inducted by using the low initial concentration of sevoflurane, compared with the high initial concentration sevoflurane (1.7%, 95%CI, 0.0% to 8.4% versus 47.7%, 95%CI, 25.5% to 70.3%, P < 0.05). The longer exposure (>3 min) of high concentration sevoflurane during induction showed higher rate of epileptiform discharges than a shorter exposure (≤3 min) (48.4%, 95%CI, 20.1% to 77.3% versus 5.7%, 95%CI, 0.00% to 23.5%; P < 0.05). No significant difference for the incidence of epileptiform discharges was observed in subgroup analysis of addition of nitrous oxide (69.2%, 95%CI, 34.0% to 95.7% versus 41.3%, 95%CI, 15.6% to 69.7%, P ﹥0.05) and type of EEG monitoring (26.9%, 95%CI, 3.8% to 60.7% versus 53.1%, 95%CI, 25.4% to 79.8%, P ﹥0.05). Conclusions: The incidence of epileptiform EEG events in children during sevoflurane anesthesia varied from 19.1%-59.2%. The low initial concentration technique and shorter exposure time of high concentration sevoflurane may be associated with a decreased incidence of these epileptiform discharges in EEG. Significance: Epileptiform EEG discharges during sevoflurane anesthesia in children should arouse clinicians' attention. The use of low initial concentration technique and shorter exposure time of high concentration sevoflurane may be associated with a lower occurrence of these paradoxical events.